2014
DOI: 10.15835/nsb.6.3.9392
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Microbial Activity and Spectro-Chemical Investigation of Ink Extracts of <i> Sepiella inermis</i> (Van Hasselt 1835)

Abstract: The crude petroleum ether and methanol ink extracts of Sepiella inermis were tested for their antimicrobial activity against human pathogenic fungi and bacteria by disc diffusion method. Spectral analysis was carried out by UV-VIS spectrophotometer, FT-IR, Raman IR and GC-MS. Of the two solvent extracts, only methanol extract was active and no activity was detected in petroleum ether extract. The human pathogenic fungus Candida albicans and bacterium Proteus vulgaris were found to be highly sensitive, with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Pertumbuhan memasuki fase stasioner setelah jam ke-12 hingga jam ke-24. Vasantharaja et al (2014) melaporkan bahwa ekstrak metanol tinta Sepiella inermis dengan menggunakan GC-MS menunjukkan adanya campuran dari struktur oligomer yang merupakan gabungan antara dihidroksi indol-2-asam karboksilat dan dihidroksiindol. Ekstrak metanol ini memiliki aktivitas penghambatan terutama terhadap bakteri Gram negatif misalnya Proteus vulgaris, Pseudomonas aeruginosa dan E. coli.…”
Section: -150 Nmunclassified
“…Pertumbuhan memasuki fase stasioner setelah jam ke-12 hingga jam ke-24. Vasantharaja et al (2014) melaporkan bahwa ekstrak metanol tinta Sepiella inermis dengan menggunakan GC-MS menunjukkan adanya campuran dari struktur oligomer yang merupakan gabungan antara dihidroksi indol-2-asam karboksilat dan dihidroksiindol. Ekstrak metanol ini memiliki aktivitas penghambatan terutama terhadap bakteri Gram negatif misalnya Proteus vulgaris, Pseudomonas aeruginosa dan E. coli.…”
Section: -150 Nmunclassified
“…However, the melanin concentration of cuttlefish ink extract (0.010 g / mL) was able to kill bacteria so that after 24-hour incubation, there was only one living cell (inhibition reached 99.99%) (Fitrial and Khotimah, 2017). Besides, Vasantharaja et al (2014) reported that methanol extracts of Sepia sp. ink using GC-MS showed a mixture of oligomeric structures, which was a combination of dihydroxy indol-2-carboxylic acid and dihydroxyindole.…”
Section: Antibacterial Testmentioning
confidence: 99%